Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/dme.14419
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and physicians’ experiences with diabetes consultations and the use of dialogue tools in the DiaPROM pilot trial: A qualitative study

Abstract: Aim To explore nurses’ and physicians’ experiences with diabetes consultations in general and the use of dialogue tools in the Diabetes Patient‐Related Outcome Measures (DiaPROM) pilot trial. Methods We used a qualitative explorative design by conducting semi‐structured in‐depth interviews with five nurses and nine physicians engaged in the DiaPROM pilot trial. The pilot trial aimed to test an intervention utilizing the patient‐reported Problem Areas In Diabetes (PAID) scale and person‐centred communication sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 28 publications
5
28
0
2
Order By: Relevance
“…Furthermore, our data emphasised the initiation of dialogue about underlying rationales behind responses to specific items, providing further insights about the young adults' lived experience. In a related study, HCPs described striving to balance recommendations for biomedical measurements with addressing young adults' emotional concerns due to limited resources and organisational challenges 17 . However, this clinical conflict was not linked to unwillingness in applying supportive, person‐centred strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our data emphasised the initiation of dialogue about underlying rationales behind responses to specific items, providing further insights about the young adults' lived experience. In a related study, HCPs described striving to balance recommendations for biomedical measurements with addressing young adults' emotional concerns due to limited resources and organisational challenges 17 . However, this clinical conflict was not linked to unwillingness in applying supportive, person‐centred strategies.…”
Section: Discussionmentioning
confidence: 99%
“…We have conducted two qualitative studies alongside the DiaPROM pilot trial to inform the quantitative findings by exploring participants' and HCPs' experiences and views on feasibility and acceptability 12 . The findings from HCP experiences are published 17 . In the present study, we aimed to explore young adults' experiences of outpatient follow‐up appointments, completing electronic PROMs, and using the PAID scale during the DiaPROM pilot trial.…”
Section: Introductionmentioning
confidence: 99%
“…It may also be that the psychologically and socially based subject matter of the research has seemed more relevant to nurses, however, studies have shown that psychological and social issues are considered to be important challenges by both diabetes nurses and doctors. [56][57][58] However, while there were more nurses who participated in the study, there was a broad consensus across disciplines in relation to the identified themes and solutions. It is also important to note that a tenant of this research model is that all perspectives are Open access considered relevant, as it is the ideas that they contribute rather than the volume of contribution that informs the co-design process.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that this PRO diabetes tool, due to the use of systematic patient involvement [ 31 , 32 ] in the design phase to address these factors, will have a high real-world acceptance among people with diabetes. Few studies similarly highlight a range of possible barriers to the optimal adoption and use of PRO tools in diabetes care by HCP [ 33 - 35 ]. As a national multidisciplinary group of HCPs was involved in all stages of the development of the PRO diabetes tool with attention to these issues, it is hypothesized that there will be a high level of adoption of this tool among people with diabetes.…”
Section: Introductionmentioning
confidence: 99%